Frecuencia y patrón de la violencia por pareja íntima antes, durante y después del embarazo - Silva, Elisabete Pereira (2011)
OBJECTIVE: To estimate the prevalence and analyze the pattern of intimate partner violence, before and during pregnancy and in the postpartum period. METHODS: This was a cohort study undertaken on 960 women aged 18 to 49 years, who were registered in the Family Health Program of the city of Recife, Northeastern Brazil, between 2005 and 2006. The women were interviewed during pregnancy and in the postpartum period, using a questionnaire adapted from the World Health Organization's Multi-country Study on Women's Health and Domestic Violence. To assess the pattern of intimate partner violence occurrences between a given time period and the subsequent period, the odds ratio (OR) was calculated with 95% confidence intervals (95%CI). RESULTS: The prevalence of intimate partner violence before, during and/or after pregnancy was estimated to be 47.4%. For the three periods separately, it was 32.4%, 31.0% and 22.6% respectively. The women who reported violence before pregnancy were 11.6 times more likely to report violence during pregnancy (95%CI: 8.3;16.2). When the women reported violence during pregnancy, the chance of reports in the postpartum period was 8.2 times higher (95%CI: 5.1;11.7). Psychological violence was more prevalent, especially during pregnancy (28.8%; 95%CI: 26.0%;31.7%). Sexual violence was less prevalent, especially after delivery (3.7%; 95%CI: 2.6%;5.0%). Physical violence diminished by almost 50% during pregnancy, in comparison with the preceding period. CONCLUSIONS: A significant proportion of women of reproductive age experience situations of intimate partner violence. The periods of prenatal and childcare consultations are opportunities for healthcare professionals to identify situations of violence.